Quality of work life programs and its influence on employee perception of procedural justice: case study of real estate company in Indonesia - Olivia Ruth Natalia; Maria Jacinta Arquisola (IDEAS: Journal of Management & Technology, 2022)
Quality of work life (QWL) is one company program that can impact employee performance, and producing more satisfied and engaged employees. PT ABC is a city property developer that implements QWL programs. The purpose of this study is to evaluate PT ABC employees’ perception about QWL, and its influence on employee perceptions of procedural justice. QWL is a program that improves employee welfare, atmosphere, and experience in the places where they work. Procedural justice is when policymakers follow the procedural rules that exist in distributing the results of its human resources programs, in this case, QWL programs.  This research used a quantitative method; data was collected using survey questionnaire. Purposive sampling was used to identify and enjoin 200 respondents to participate. The results of this study show that the QWL dimensions that are perceived dissatisfactory and needs improvement are adequate and fair compensation, growth and security and total life space. These four dimensions have significant positive effect on perceptions of procedural justice. This research contributes to identifying areas of QWL that need to be given attention and have implications for organizations to improve the working conditions of employees in Indonesia.